Sensitivity Analysis of Multi-Temporal Sentinel-1 SAR Parameters to Crop Height and Canopy Coverage - Nasirzadehdizaji, Rouhollah; Sanli, Fusun Balik; Abdikan, Saygin; Cakir, Ziyadin; Sekertekin, Aliihsan; Ustuner, Mustafa (MDPI, 2019)
The Polarimetric Synthetic Aperture Radar technique has provided various opportunities and challenges in agricultural activities mainly on crop management. The aim of this study is to investigate the sensitivity of 10 parameters derived from multi-temporal Sentinel-1 Synthetic Aperture Radar (SAR) data, to crop height and canopy coverage (CC) of maize, sunflower, and wheat. The correlation coefficient values indicate a high correlation for maize during the early growing stage. The coefficient determinations (R-2) of 0.82 and 0.81 indicate that there is a strong relationship between the maize height and SAR parameters including VV + VH and VV, respectively. The maize CC is well correlated with VV parameter (R-2 = 0.73), but it is observed that at the later growing stage the correlation became weaker. This means that the sensitivity decreases with increasing vegetation cover growth. Compared to maize, the sensitivity of SAR parameters to wheat variables is often good at the early stage. However, the highest correlation with wheat height represented by Alpha (alpha) decomposition parameter (R-2 = 0.67). The sunflower height has an insignificant correlation with the majority of SAR parameters and only VH polarization shows low sensitivity (R-2 = 0.31). The sunflower CC shows relatively higher correlation with VV polarization (R-2 = 0.46) at the early stage while no considerable correlation is observed at the later stage. It is found that Sentinel-1 has a high potential for estimation of crop height and CC of the maize as a broad-leaf crop. The same is not true for sunflower as another broad-leaf crop.
Keywords: PolSAR; Sentinel-1 dual polarimetric SAR; scattering coefficient; agricultural monitoring; crop variables; RADARSAT-2 POLARIMETRIC SAR; BACKSCATTERING COEFFICIENT; CORN; DECOMPOSITION; Chemistry; Engineering; Materials Science; Physics